SUFI WOMEN IN ISLAM (on the basis of foreign researches) - Ismoilov Kahramonjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, chaste Sufi women who lived in worship with the love of God in the Islamic world are compared with the researches of foreign scientists. It mentions Rabia Adawiya, Fatimah Raziya, Zainab bini Abu-l-Barakat, Fatimah Jahanaro, Zebinisa and Ziynatunnisal.